Social Enterprises through Traditional Cooperation: Love, Joint Responsibility, Portfolio, and Wellbeing - Junaedi, I Wayan Ruspendi; Damayana, I Wayan; Waruwu, Dermawan; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2020)
This research aims to explain how the cultural values ??of society and organizational culture can influence the increase in social entrepreneurial activities, how entrepreneurial activities can affect the dimensions of sustainable development. How to contextualize resource dependency theory in the perspective of social entrepreneurship associated with sustainable development, as well as to construct a model of social entrepreneurship based on sustainable development, including new dimensions in measuring it. The research method used is a qualitative research method by doing; observations, interviews with CU Betang ASI Management, business owners, and family business managers and documentation. The success of CU in developing its social enterprises lies in love, joint responsibility, and portfolios based on community culture and the environment. This research has succeeded in explaining the contextualization of resource dependency theory related to how social enterprises develop their environmentally based businesses using resource dependency theory expanded from an institutional perspective where social enterprises engage in joint ventures with the communities they develop. Through this research, there is an opportunity to use this theory in the realm of an embedded organization. For the aspect of sustainable development, there are 3 main dimensions, namely love, striving for and maintaining, and dimensions of wellbeing with each indicator. Future research will of course need to be carried out to confirm this model using both positivistic and mixed approaches